Occurrence of Sharp Hydrogen Effusion Peaks of Hydrogenated Amorphous Silicon Film and Its Connection to Void Structures. Issue 9 (28th May 2020) - Jafari, Sahar; Steffens, Jonathan; Wendt, Michael; Terheiden, Barbara; Meyer, Sylke; Lausch, Dominik
Abstract : The amount of hydrogen released from plasma‐enhanced chemical vapor (PECVD) deposited hydrogenated amorphous silicon (a‐Si:H) layers is determined by gas effusion measurements. A sharp peak (SP) is observed in the effusion spectra of samples with substrate temperature T S  ≥ 200 °C. Light microscopic images indicate the formation of bubbles after deposition for all samples and film deterioration after effusion measurement in correlation with the presence of the hydrogen SPs. Change in substrate temperature varies with the microstructure of the film, the hydrogen concentration, and the density. A low T S leads to a porous structure with large number of interface bubbles, and therefore no hydrogen‐induced SP appears during hydrogen effusion. Whereas high T S causes a compact a‐Si:H film in which the hydrogen effusion is limited by the longer diffusion, while the number of interface bubbles decreases. The storage of near substrate hydrogen in the bubbles in compact material leads to a local explosion by increase in excessive pressure. The difference between the low temperature peak and the position of the SP in the effusion spectra indicates the time required to fill the interface bubbles with hydrogen, which decreases with increasing film density, suggesting that the volume of the interface bubble decreases. Abstract : A sharp hydrogen peak is observed in the effusion spectra of a‐Si:H film deposited at high substrate temperatures. A critical pressure of hydrogen storage induced by annealing leads to film deterioration in high density films. The substrate temperature during deposition plays a key role in the void structure and influences the thermal behavior of the film at elevated temperature.